Description of the final stadium larva of Cryptophaea vietnamensis (van Tol & Rozendaal, 1995) (Odonata: Euphaeidae) from Vietnam - Phan, Quoc Toan; Keetapithchayakul, Tosaphol Saetung (Zootaxa, 2024)
The final stadium larva of the Cryptophaea vietnamensis (van Tol & Rozendaal, 1995) from Vietnam is described and illustrated based on specimens reared to adulthood. This is the first record of a larva of the genus Cryptophaea Hämäläinen, 2003. The larvae of C. vietnamensis are seldom encountered, but where present they may co-occur with larvae of the genera Anisopleura Selys, 1853, Bayadera Selys, 1853, and Euphaea Selys, 1840. The larvae of Cryptophaea are very similar to those of Bayadera but can be separated from known larvae of that genus by the distal margin of the ligula being a pronounced bilobed structure and the spurs on outer margin of mandible being poorly developed.